2016
DOI: 10.1039/c5ta10492k
|View full text |Cite
|
Sign up to set email alerts
|

Pt/C–LiCoO2composites with ultralow Pt loadings as synergistic bifunctional electrocatalysts for oxygen reduction and evolution reactions

Abstract: A composite material with ultralow Pt loading showed excellent bifunctionality for the ORR and OER due to a synergistic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…However, the commercialization of these fuel cells is still hampered by the high cost and the poor stability of the Pt‐based oxygen reduction reaction (ORR) electrocatalysts. These limitations stimulated the search for alternative electrocatalysts for the ORR with lower Pt loadings or, preferably, devoid of noble metals . Initially, the attempts mainly focused on pyrolyzed carbon‐supported transition metal complexes, but neither the stability nor the activity of these electrocatalysts reached the desired levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, the commercialization of these fuel cells is still hampered by the high cost and the poor stability of the Pt‐based oxygen reduction reaction (ORR) electrocatalysts. These limitations stimulated the search for alternative electrocatalysts for the ORR with lower Pt loadings or, preferably, devoid of noble metals . Initially, the attempts mainly focused on pyrolyzed carbon‐supported transition metal complexes, but neither the stability nor the activity of these electrocatalysts reached the desired levels.…”
Section: Introductionmentioning
confidence: 99%
“…(Table S4, Supporting Information). We demonstrated that the novel Pt‐based N‐CNµS electrocatalysts (nucleation time: 50 ms) generated a mass activity (up to 0.1 A mg −1 Pt at −0.2 V vs SCE) which is considered to be promising based on some reported values for commercial catalysts . Besides Pt group metals, transition metal oxides also have been widely used for the ORR, and some of catalysts like Co 3 O 4, Mn 3 O 4 , and Mo–Co spinel oxides, are reported having excellent catalytic activities toward ORR (Table S4, Supporting Information).…”
Section: Resultsmentioning
confidence: 91%
“…The structural characterization of the oxides by XRD using the High Score X`Pert software and the ICDD database, led to a classification according to the reference materials LiCoO2 ICSD code: 00-016-0427 with rhombohedral geometry and space group R-3m (166) and LiMn2O4 ICSD code: 00-018-0736, with cubic geometry and space group Fm-3m (225), according to preliminary works [11][12]. The crystallite size was obtained by means of the Debye-Scherrer equation, resulting in the presence of nanometric crystallites in the range of 5-8nm, using the most intense diffraction signals in each case.…”
Section: Resultsmentioning
confidence: 99%